"Zgodovina ne teče naravnost, cikcakasto gre" - Prosenc, Irena (Ars et humanitas, 2012)
In his novel Blindly Claudio Magris develops a complex perception of time. This perception is intertwined with reflections on history, identity and the status of the narrative voice. History, which "is not linear" but "zigzags" is presented as a continuously repetitive phenomenon, while temporal time is impossible to measure. The status of the autodiegetic narrator becomes highly problematic as the narrative voice assumes identities belonging to various historical periods ranging from the late 18th to the 20th centuries. The novel focuses on repressive historical periods which deform the protagonists' identities, thereby conveying an image of history as a blind and violent force. Fragmentation, one of the basic narrative techniques in the novel, concerns time sequences as well as the protagonists' identities and the narrative voice itself. As the protagonists' lives can only be narrated as fragments, there are frequent passages between different time periods. These merge into extratemporality, which is associated with eternal suffering stemming from the repetitive, oppressive nature of history. The historical events depicted in the novel are interpreted through the extratemporal dimension of the Argonaut myth.
Keywords: Italian literature; Magris, Claudio, 1939-; Italian novel; "Alla cieca"; italijanska književnost; time; italijanski roman; history; identity; 20.st.; čas; myth; Argonauts; zgodovina; identiteta; mythology; miti; Argonavti